2013
DOI: 10.1177/1012690213485951
|View full text |Cite
|
Sign up to set email alerts
|

Natural disaster arrhythmia and action sports: The case of the Christchurch earthquake

Abstract: Taking inspiration from French sociologist and philosopher Henri Lefebvre's theory of 'rhythmanalysis', the author advocates new ways of thinking about the impact of natural disaster on the bodies and everyday mobilities of those who continue to live in disrupted spaces. Drawing upon interviews conducted with residents living in Christchurch, New Zealand, before, during and after the devastating February 2011 earthquake, she explains how this 'arrhythmic' experience forced many to rethink the importance of spo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 38 publications
1
25
0
4
Order By: Relevance
“…For example, Dyck (2011) highlighted how sport can cause harm by reinforcing hierarchies and gender inequality, and thus its use should be carefully considered within context. Others pointed out inherent selection biases (Rhodes, 2015), noted how sporting activities were just one piece of a larger rehabilitation plan (Ley et al, 2018), suggested that the use of sporting activities assumes able-bodism and at least some form of social power (Thorpe, 2015, 2016; Thorpe & Ahmad, 2015), and that participants who have experienced trauma often have narratives that remain unresolved (van Ingen, 2016). Thus, collectively the limitations acknowledged by these studies reinforce that sporting activities are not a panacea, particularly for those who have experienced trauma.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…For example, Dyck (2011) highlighted how sport can cause harm by reinforcing hierarchies and gender inequality, and thus its use should be carefully considered within context. Others pointed out inherent selection biases (Rhodes, 2015), noted how sporting activities were just one piece of a larger rehabilitation plan (Ley et al, 2018), suggested that the use of sporting activities assumes able-bodism and at least some form of social power (Thorpe, 2015, 2016; Thorpe & Ahmad, 2015), and that participants who have experienced trauma often have narratives that remain unresolved (van Ingen, 2016). Thus, collectively the limitations acknowledged by these studies reinforce that sporting activities are not a panacea, particularly for those who have experienced trauma.…”
Section: Resultsmentioning
confidence: 99%
“…With a less explicit connection between philosophical and theoretical positioning of the research, and a more pronounced disciplinary focus, the work of others both explicitly (Ley et al, 2018) and implicitly (Dyck, 2011;Ratcliff et al, 2002;Spaaij, 2015;Sobotova et al, 2016;Thorpe, 2015;Thorpe & Ahmad, 2015) together, these studies represent a less critical approach in which sporting activities are assumed to provide benefits, without critically addressing various other factors at play.…”
Section: Meta-theorymentioning
confidence: 99%
See 2 more Smart Citations
“…Academic interest in ASDP is growing (Thorpe, 2013; Thorpe & Rinehart, 2013; Wheaton, 2013; Wheaton et al, 2017). Thorpe finds ASDP programs operate within alternative development frameworks and “thus they offer valuable insights for those in the SDP community interested in developing more critical interventions that contribute to more fundamental systemic changes in social life” (p. 5).…”
Section: Literature Reviewmentioning
confidence: 99%